Preclinical Performance Evaluation of Percutaneous Glucose Biosensors: Experimental Considerations and Recommendations - Soto, Robert J. (J Diabetes Sci Technol, 2015)
The utility of continuous glucose monitoring devices remains limited by an obstinate foreign body response (FBR) that degrades the analytical performance of the in vivo sensor. A number of novel materials that resist or delay the FBR have been proposed as outer, tissue-contacting glucose sensor membranes as a strategy to improve sensor accuracy. Traditionally, researchers have examined the ability of a material to minimize the host response by assessing adsorbed cell morphology and tissue histology. However, these techniques do not adequately predict in vivo glucose sensor function, necessitating sensor performance evaluation in a relevant animal model prior to human testing. Herein, the effects of critical experimental parameters, including the animal model and data processing methods, on the reliability and usefulness of preclinical sensor performance data are considered.